2013
DOI: 10.1016/j.heares.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

ECAP spread of excitation with virtual channels and physical electrodes

Abstract: The primary goal of this study was to evaluate physiological spatial excitation patterns for stimulation of adjacent physical electrodes and intermediate virtual channels. Two experiments were conducted that utilized electrically evoked compound action potential (ECAP) spread-of-excitation (SOE) functions obtained with the traditional forward-masking subtraction method. These two experiments examined spatial excitation patterns for virtual-channel maskers and probes, respectively. In Experiment 1, ECAP SOE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 22 publications
7
34
0
1
Order By: Relevance
“…To determine whether the ECAP spatial separation (R) itself was significantly different across electrode regions (basal, middle, or apical) a one-way RM-ANOVA was performed. Results revealed no significant main effect of electrode region (F[1,9] ¼ 0.83, p ¼ 0.39) on ECAP R, consistent with the larger data set previously reported by Hughes et al (2013). Figure 3 displays scatter plots of group mean pitchranking thresholds (a) versus ECAP separation indices (R) for basal, middle, and apical electrode regions (top to bottom, respectively).…”
Section: Pitch Ranking (A)supporting
confidence: 84%
See 4 more Smart Citations
“…To determine whether the ECAP spatial separation (R) itself was significantly different across electrode regions (basal, middle, or apical) a one-way RM-ANOVA was performed. Results revealed no significant main effect of electrode region (F[1,9] ¼ 0.83, p ¼ 0.39) on ECAP R, consistent with the larger data set previously reported by Hughes et al (2013). Figure 3 displays scatter plots of group mean pitchranking thresholds (a) versus ECAP separation indices (R) for basal, middle, and apical electrode regions (top to bottom, respectively).…”
Section: Pitch Ranking (A)supporting
confidence: 84%
“…More recently, Hughes and Goulson (2011) determined that virtual-channel SOE amplitudes fall approximately half-way between the amplitudes of adjacent physical electrodes for both dualelectrode mode and current steering. Hughes et al (2013) showed that spatial separation of SOE patterns was greater between adjacent physical electrodes than between the intermediate virtual channels and the flanking physical electrodes, indicating measurable separation between neural populations. Therefore, it seems conceivable that the ECAP SOE could be used as an objective tool to assist in predicting behavioral perception of virtual channels.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations